Abuse of Authority Article 3 of Law No. 31 of 1999 concerning Eradication of Corruption in Criminal Law Review (Law Research Review Quarterly, 2019)
Research on the concept of abuse of authority in the Constitution of Corruption in Indonesia, describes the problem together with the concept of abuse of authority in court decisions. The elaboration with normative research methods ultimately results in showing that the formulation of violations in Article 3 of the PTPK Law is inconsistent. The location of inconsistency is the first element of violation ("with the aim of enriching oneself, others, or corporations") formulated in the material, while the 3rd element ("may endanger the country's finances or economy") is formulated formally. On this basis, the elements of violation "abuse the authority, opportunity, or means they have because of their position / position". As a solution, presumably with the nature given in the haeren between the concept of "haram" with the concept of "abuse of authority" and in practice evidence of abuse of authority is difficult, because assessing the abuse of authority related to factual, it is recommended for Article 3 of Law No. 31 of 1999 jo. UU no. 20 of 2001 just deleted. Another reason is: the element of violation of the law in Article 2 of Law no. 31 of 1999 jo. Law Number 20 of 2001 has been able to accommodate the elements of "abuse of authority", because "abuse of authority" is the "species" of the "genus" element of "breaking the law".